Relative importance of cigarette smoking in occupational lung disease. Issue 1 (February 1981) - Elmes, P C
Abstract : Since 1900 respiratory disease has remained a constant serious cause of chronic ill health and premature death in Britain. The falling importance of tuberculosis and pneumonia has been off-set by the rise in lung cancer. Bronchitis morbidity and mortality have fallen only slightly since 1935. To produce any real improvement in the future existing information as to cause must be studied. The relative contribution of occupational exposure is compared with the importance of cigarette smoking. Relevant information is scanty and has been produced to emphasise the existence of occupational diseases rather than assess their importance to the community as whole. In Britain the evidence is that within the coal mining and iron and steel industries conditions are now such that dust exposure contributes little to the morbidity or mortality compared with the workers' smoking habits. Similar results have been shown by a cross-sectional survey of many dusty occupations in Western Germany. Only in the disappearing Welsh slate industry has dust disease been at least as important as smoking. Until the current regulations were introduced conditions existed among asbestos workers such that the combined effect of cigarette smoking and dust exposure led to a loss of life expectation of over 10 years in moderate smokers. Since the new regulations were introduced the risk for asbestos workers should approximate to that for other industrial workers. While control of occupational exposure to respiratory hazards remains important, a far greater improvement to respiratory health would be produced by controlling tobacco smoking.